Under the humble mask: Investigating when and how leader-expressed humility leads to employee voice - Zou, Wen-Qian; Chen, Shu-Chen (Frontiers in Psychology, 2022)
This study aimed to explore the psychological mechanisms through which psychological safety and self-efficacy mediate the relationship between leader-expressed humility and employee voice. Moreover, attribution theory was applied to examine the possible detrimental effects of leader-expressed humility when employees perceive manipulative intentions in their humble leader. The current study proposed the leader’s manipulative intention as a moderator to weaken the indirect relationships between leader-expressed humility and employee voice through psychological safety and self-efficacy. Time-lagged supervisor–subordinate matched data were used to test the model. Our findings reveal leader’s manipulative intention weakens the positive effect that leader-expressed humility impacts on employee voice through psychological safety and self-efficacy. The implications of the findings were discussed from both theoretical and practical perspectives.